Development of Smart Apps Creator-Based Interactive Learning Media to Support 21st Century Skills in Pancasila Education for Elementary Schools - Anggraeni, Aisyah; Erita, Yeni; Nora, Desri; Rahmi, Ulfia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
Abstract: This research aims to develop interactive learning media based on Smart Apps Creator to support 21st-century skills in Pancasila education for elementary school students that are feasible, practical, and effective. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included fifth-grade teachers and students from selected elementary schools in Padang, West Sumatra. The selection of research subjects was conducted purposively, considering factors such as implementing the Merdeka Curriculum, availability of technological infrastructure, and the schools’ willingness to collaborate. Data were collected through observations, interviews, questionnaires, and learning outcome tests. Both qualitative and quantitative data analyses were used, including n-gain score analysis. The development resulted in an interactive media product for Pancasila education using Smart Apps Creator, which was declared feasible, practical, and effective. The feasibility assessment by material, linguistic, and media experts obtained an average score of 91.67%, categorized as very feasible. The practicality aspect, evaluated through teacher 90%, indicating a very practical product, and student responses achieved an average score of 96,6%, indicating a very practical product. The average N-gain score in the experimental class was 85.11 (high category), while the control class scored 44.57 (moderate category). These findings indicate that the developed interactive media effectively supports the enhancement of 21st-century skills, particularly in Pancasila learning for elementary students.